Loneliness and low life satisfaction associated with older adults’ poor oral health - Finlayson, T. L.; Moss, K. L.; Jones, J. A.; Preisser, J. S.; Weintraub, J. A. (Frontiers in Public Health, 2024)
Objective: To examine the association of older adults’ loneliness, life satisfaction, and other psychological stressors and resources with oral health status. Methods: This study merged 2018 data from the Health and Retirement Study (HRS) CORE survey with the HRS-Dental Module, and Psychosocial and Lifestyle Questionnaire–Panel A “Leave Behind” surveys (HRS-LB)(N=418). Dental Module outcomes of interest were self-rated oral health status (SROH), and oral health-related quality of life (OHQOL). Older adults reported on loneliness, life satisfaction, perceived age, social status, control, mastery, and chronic stressors. Three distinct profiles based on the distribution of loneliness and life satisfaction were previously identified in the combined HRS and HRS-LB study population (N=4703) using latent class analysis (LCA). Class A:“Not Lonely/Satisfied” adults had the fewest psychosocial risk factors and most resources; Class C:“Lonely/Unsatisfied” adults exhibited the opposite profile (most risk factors, fewest resources); Class B:“Lonely/Satisfied” adults exhibited loneliness with favorable life satisfaction. Regression models examined associations between LCA classes and fair/poor SROH and OHQOL score and individual items, after adjusting for socio-demographics. Results: About 13% of older adults experienced loneliness, and about 16% reported low life satisfaction. About one-quarter (28%) of older adults reported fair/poor SROH, and they experienced more psychosocial risk factors than their counterparts with better oral health status. Nearly half the older adults were categorized in Class A:“Not Lonely/Satisfied”(n=201), and about one-quarter each in Class B:“Lonely/Satisfied”(n=103) and Class C:“Lonely/Unsatisfied”(n=112). In fully adjusted models, Class B older adults had 1.81 (1.11-2.96) times greater odds of fair/poor SROH, and Class C had 4.64 (2.78-7.73) times greater odds of fair/poor SROH than Class A. Fully adjusted linear regression model results indicated a gradient by LCA class. OHQOL varied; Class A older adults had the best/lowest OHQOL score (mean=8.22, 4.37-12.10), Class B scored in the middle (mean=12.00, 7.61-16.50), while Class C had the worst/highest OHQOL score (mean=16.20, 11.80-20.60). Conclusions: Loneliness, as a defining characteristic distinguishing three latent classes of older adults, was associated with more risk factors and poorer oral health outcomes. Loneliness, life satisfaction, perceived age, social status, control, mastery, and chronic stressors vary widely for older adults and matter for oral health and OHQOL.